1976
DOI: 10.1063/1.432962
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rate of the reaction of atomic hydrogen with acetaldehyde

Abstract: Absolute rate constants for the reaction of hydrogen atoms with acetaldehyde were obtained over the temperature range 298-500 K using the flash photolysis-resonance fluorescence technique. The rate constants gave the Arrhenius expression k = (2.23 ±0.39)X 10-11 exp( -3300± 120/ 1.987 T) cm 3 molecule-Is-I. Independent experiments with a discharge flow system employing resonance fluorescence detection of H gave a room temperature rate constant in agreement with this equation. These results are discussed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…= 1.9 f 0.2 over the limited temperature range of 298-360 K. Thus HC1 appears to be slightly less effective as a third body in reaction (2) than H2O ( a = 2.9) [17], but more effective than SFG ( a = 1.2) [17]. The results for HC1 are similar to those reported for the rare gases [15] and nitrogen [21] as third bodies in reaction (2), in as much as they give very similar temperature dependences for k.2 (that is, a is independent of temperature), and which were interpreted in terms of an energy transfer mechanism [15]. If a radical molecule complex mechanism [22] were to occur for M = HC1, the temperature dependence of k2 would be different, and probably more negative, than for M = N2O…”
Section: R~l [ M ]supporting
confidence: 88%
“…= 1.9 f 0.2 over the limited temperature range of 298-360 K. Thus HC1 appears to be slightly less effective as a third body in reaction (2) than H2O ( a = 2.9) [17], but more effective than SFG ( a = 1.2) [17]. The results for HC1 are similar to those reported for the rare gases [15] and nitrogen [21] as third bodies in reaction (2), in as much as they give very similar temperature dependences for k.2 (that is, a is independent of temperature), and which were interpreted in terms of an energy transfer mechanism [15]. If a radical molecule complex mechanism [22] were to occur for M = HC1, the temperature dependence of k2 would be different, and probably more negative, than for M = N2O…”
Section: R~l [ M ]supporting
confidence: 88%
“…3a. Also, even if reactions (1)-(3) were used as the initiation reaction and various rate-constant expressions for reactions, (1)-(3), (5), (7), and (17) were assumed, the UV-absorption profiles at 200 nm and the IRemission profiles at 4.68 µm were not reproduced and the calculated values were much smaller than observed ones, as shown in Figs. 3a and 4a; the UVabsorption profiles and the IR-emission profiles largely depended on ketene concentration produced, as shown cm 3 mol −1 s −1 was assumed for reaction (12).…”
Section: Ch 3 Cho Reactionmentioning
confidence: 81%
“…The effective heating times at each temperature are 2850 µs (1000 K), 2630 µs (1100 K), 2410 µs (1200 K), 2190 µs (1300 K), 1970 µs (1400 K), 1750 µs (1500 K), 1520 µs (1600 K), and 1300 µs (1700 K). ---: calculated with the mechanism described in Table XII; · · · · · · · · · · · · · · ·: reactions (1), (5), (7), and (17) and the rate constant values reported by Baulch et al [37,38]; ------: reactions (1), (5), (7), (17) and CH 3 CHO + CHO = CH 3 CO + CH 2 O and the rate constant values reported by Dagaut et al [14]; -·-·-·-·: calculated with the mechanism described in Table XII •: observed at 1329 K, 1.97 atm, 1.81 × 10 −5 mol/cm 3 ; : observed at 1477 K, 2.37 atm, 1.96 × 10 −5 mol/cm 3 ; , observed at 1589 K, 2.68 atm, 2.05 × 10 −5 mol/cm 3 ;---: calculated with the mechanism described in Table XII; · · · · · · · · · reactions (1), (5), (7), and (17) and the rate constant values reported by Baulch et al [37,38]; -·-·-·-·-: calculated with the mechanism described in Table XII decreased with time. The profiles were analyzed using an equation A t = log (I f /I t ) / log (I f /I 0 ), where I f was the signal voltage corresponding to the full intensity and I 0 and I t were the signal voltages corresponding to the absorption intensities at the reflected shock front (t = 0) and at time t, respectively.…”
Section: Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations